Mathematical writing ability in Problem Based Learning observed from the level of logical-mathematical intelligence - Virgonanto, Titis Hari; Pujiastuti, Emi; Prabowo, Ardhi (Unnes Journal of Mathematics Education, 2019)
The purpose of this study were to (1) prove the students' mathematical writing ability in the application of PBL achieve classical mastery criteria; (2) describe the mathematical writing ability of students in PBL observed from the level of logical-mathematical intelligence. The research used a mixed-method. The population of this study was 278 VIIth grade students in SMP 4 Kudus. The sample in this study was 32 students of VII-A class. Quantitative data sampling was done using simple random sampling technique. Quantitative data were obtained using tests. Quantitative data analysis used the normality test, homogeneity test, t-test, and z-test. The subjects in this study were 6 students. Qualitative data analysis was the analysis of data from interviews. The results showed that (1) the mathematical writing ability of VIIth grade students observed from the level of logical-mathematical intelligence achieved classical mastery criteria; (2) Students with high, moderate and low logical- mathematical intelligence levels met all three aspects of their mathematical writing ability, such as written text, drawing, and mathematical expression.